ANDROID-BASED SPIN COATING MONITORING - Ismangil, Agus; Nanang, Nanang (Instrumentasi, 2023)
The spin coating technique can produce very thin layers by utilizing centrifugal force,linear shear stress and uniform evaporation of the solution on a rotating disk or substrate.The thin layer produced by the spin coating method has a high level of homogeneity. Thedesired thickness and quality of the coating can be controlled based on the viscosity orviscosity of the solution, material content, time, and speed of rotation of the spin coater.The research method used to develop this research is the instrumentation research methodof the spin coating device which detects spin on the disc. This system uses an ESP32Microcontroller, Hall effect Magnet Sensor, Diodes, DC Motor, LCD 165x2 i2c, Mosfetand smartphone. The results obtained are that this Spin Coating tool can rotate with amaximum speed of 3000 rpm, and a minimum speed of 1000 rpm. Although there is stillnoise at certain speeds caused by the less stable data transmission process and lesssensitive response from the sensor, as a whole, the spin coating tool can rotate at a certainspeed by monitoring using android.